2015
DOI: 10.4236/msce.2015.37005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu Doped ZnO Nanoparticles: Crystallographic, Optical, FTIR, Morphological and Photocatalytic Study

Abstract: Nanoparticles of Zn1−xCuxO system with nominal compositions x = 0.0, 0.01, 0.02 and 0.03 were prepared by co-precipitation method at room temperature. Structural, morphological, optical and chemical species of grown crystals were investigated by X-ray diffraction (XRD) technique, Scanning Electron Microscopy (SEM), UV-visible and FTIR spectroscopy, respectively. XRD analysis confirms that all samples have hexagonal structure with no impurity phases which suggest that Cu ion successfully incorporated into the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 30 publications
4
27
0
2
Order By: Relevance
“…It can be seen that the absorption edge shows a clear red‐shift from 4.03 to 2.93 with the increase of Cu 2+ concentration. This decrease in energy band gap for ZnO:Cu NPs correspond to p‐d spin exchange interactions between the ZnO band electrons and the localized d electrons of doped Cu 2+ and have been observed in different reports . The PL intensity of the trap state emissions of ZnO NPs was quenched with the introduction of Cu impurity to the ZnO lattice, as shown in Figure (b) and a Cu‐related emission due to transition of electrons from trap states (I Zn ) to T 2 acceptor level appeared which showed a clearly red‐shift from 485 to 520 nm.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…It can be seen that the absorption edge shows a clear red‐shift from 4.03 to 2.93 with the increase of Cu 2+ concentration. This decrease in energy band gap for ZnO:Cu NPs correspond to p‐d spin exchange interactions between the ZnO band electrons and the localized d electrons of doped Cu 2+ and have been observed in different reports . The PL intensity of the trap state emissions of ZnO NPs was quenched with the introduction of Cu impurity to the ZnO lattice, as shown in Figure (b) and a Cu‐related emission due to transition of electrons from trap states (I Zn ) to T 2 acceptor level appeared which showed a clearly red‐shift from 485 to 520 nm.…”
Section: Resultssupporting
confidence: 55%
“…Fu et al reported 88% degradation of MO in the presence of ZnO:Cu NPs under 25 W UV lamp within 240 min. Mittal et al reported 78.8% degradation of crystal violet solution in the presence of ZnO:Cu NPs under 250 W mercury lamp within 3.5 h. Labhane and coworkers reported 60% degradation of methylene blue in the presence of ZnO:Cu NPs under 25 W UV lamp within 4.5 h. Moreover Cu‐doping does show a decrease in photocatalytic activities of doped NPs compared to undoped counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations